Implementation of Islamic Religious Education Learning in Shaping Students' Muslim Personality at Indah Integrated Islamic Private Junior High School Medan - Hasibuan, Mahyuman; Budianti, Yusnaili; Al Farabi , Mohammad (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This research will describe how implementing Islamic religious education shapes the Muslim personalities of students at the Indah Integrated Islamic Private Junior High School in Medan. The method used in this research is qualitative. The subjects determined in this study are Islamic religious education teachers. Then, the author uses interviews, observation, and documentation in the data collection. While the technical analysis that the author uses involves data reduction techniques, data presentation, and conclusion drawing, the results showed that implementing Islamic religious education has a positive effect on forming students' personalities. Students become better in terms of attitude, behaviour, and morals. First, the Islamic religious education curriculum at Indah Integrated Islamic Private Junior High School focuses on developing a comprehensive understanding of Islamic values and teachings. Secondly, the school uses an integrated approach to religious education, integrating religious and academic learning. Thirdly, this integrated approach successfully instils moral and ethical values alongside academic knowledge. Fourthly, the school's efforts in promoting Islamic education are visible in students' behaviour and learning.